VITAMIN A SUPPLEMENTATION COVERAGE AND PREVALENCE OF MALNUTRITION STATUS AMONG TODDLERS IN SIDOARJO, INDONESIA: Cakupan Pemberian Vitamin A dan Kejadian Status Gizi Buruk pada Balita di Sidoarjo, Indonesia - Ghanynafi, Abdullah; Novita Sari, Siti Shofiya; Astutik, Erni; Farihatin Hasanah, Ganjar Nailil (Universitas Airlangga, 2024)
Background: A toddler's nutrition status is an essential indicator of public welfare, and the occurrence of malnutrition leads to severe problems that impact child growth development. Purpose: This research aims to understand the coverage correlation of giving vitamin A with the occurrence of malnutrition among toddlers in Sidoarjo regency. Methods: The researchers used ecological study methods followed by the usage of secondary data retrieved from Sidoarjo's Regency Health Profile in 2020-2022 with a sub-district analysis unit. Vitamin A coverage and the nutrition status amount by sub-district were visualized on the map using QGIS. Pearson's correlation test was used to find out the correlation between coverage of giving vitamin A and nutrition status. Results: The findings show that there are none of the significant correlations found between giving vitamin A and the occurrence of malnutrition in toddlers, which tends to increase annually. Conclusion: Therefore, it can be concluded that there is no significant correlation between the coverage of vitamin A and the occurrence of malnutrition among toddlers, which indicates there are a few factors and risks that play an essential role in participating in the impact of malnutrition status among toddlers in Sidoarjo regency.